2013
DOI: 10.1245/s10434-013-2957-y
|View full text |Cite
|
Sign up to set email alerts
|

Delay to Curative Surgery Greater than 12 Weeks Is Associated with Increased Mortality in Patients with Colorectal and Breast Cancer but Not Lung or Thyroid Cancer

Abstract: Delays to curative surgery beyond 12 weeks were associated with increased mortality in colorectal and breast cancers, suggesting that health provision services should be organized to avoid unnecessary treatment delays. Health care systems should also aim to reduce socioeconomic and geographic disparities and to guarantee equitable access to high quality cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(163 citation statements)
references
References 33 publications
5
153
1
4
Order By: Relevance
“…Estudo que avaliou o impacto da demora da realização de cirurgia com finalidade curativa na sobrevida concluiu que, no câncer de mama, intervalos superiores a 12 semanas estão associados ao aumento da mortalidade pela doença 13 . Em contrapartida, análise retrospectiva realizada no Reino Unido obteve resultado diferente dos demais estudos ao sugerir que atrasos superiores a 60 dias não prejudicam significativamente a sobrevivência e que os pacientes que receberam tratamento dentro de um período de 30 dias apresentaram piores resultados do que os que foram tratados em períodos mais tardios 7 .…”
Section: This Study Aimed To Analyze the Time Elapsed Between Breast unclassified
“…Estudo que avaliou o impacto da demora da realização de cirurgia com finalidade curativa na sobrevida concluiu que, no câncer de mama, intervalos superiores a 12 semanas estão associados ao aumento da mortalidade pela doença 13 . Em contrapartida, análise retrospectiva realizada no Reino Unido obteve resultado diferente dos demais estudos ao sugerir que atrasos superiores a 60 dias não prejudicam significativamente a sobrevivência e que os pacientes que receberam tratamento dentro de um período de 30 dias apresentaram piores resultados do que os que foram tratados em períodos mais tardios 7 .…”
Section: This Study Aimed To Analyze the Time Elapsed Between Breast unclassified
“…O atraso no diagnóstico e no tratamento do câncer de mama pode propiciar estágio mais avançado da doença, resultando em tratamento mais agressivo, com pior prognóstico e consequente aumento da mortalidade 4,5 O principal intervalo de tempo estudado foi definido como tempo total, que compreende o período entre a data da primeira detecção da alteração na mama sugestiva de neoplasia e o início do tratamento específico (cirurgia ou quimioterapia neoadjuvante). Esse intervalo foi subdividido em dois: tempo atribuído à paciente, que abrange o intervalo entre a detecção do primeiro sintoma e a primeira consulta motivada pela anormalidade na mama; tempo atribuído ao serviço, que compreende o período entre a primeira consulta e o início do tratamento.…”
Section: Introductionunclassified
“…A delay in CRC surgery of >12 weeks is associated with an adjusted hazard ratio (HR) of 2.65 for all-cause mortality. 54 Halpern et al noted that black and Hispanic patients were less likely to receive treatments on time, across several tumor types, and suggested that Original Article such delays may account for suboptimal outcomes in the minorities studied. 55 In a cohort of 12,181 patients with a diagnosis of CRC who were followed between 1995 and 2007, Wassira et al observed a higher incidence of advanced disease in black and Hispanic individuals compared with white patients, as well as higher mortality in the same subgroups.…”
Section: Delays In Diagnosismentioning
confidence: 99%